2020
DOI: 10.1007/s10745-020-00190-0
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perceptions as a Driver of Agricultural Practices: Understanding Soil Fertility Management Practices in Cocoa Agroforestry Systems in Cameroon

Abstract: In Africa, cocoa yields are low, partly due to soil fertility constraints and poor management. While peoples’ knowledge, aspirations, and abilities are key factors explaining their behaviour, little is known about the rationales that underpin soil fertility management practices (SFMPs) of cocoa farmers. To address this gap, we conducted an exploratory survey in two contrasting regions in Cameroon where cocoa is an important crop: the humid forest and the forest-savannah transition zone. Some 30% of farmers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 38 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Kebede, Baudron [58] found that the loss of soil fertility, and the subsequent negative impact on yields, combined with a need to sustain food production by the national level policy makers, is an important driver of agricultural expansion in the southern parts of Ethiopia. A similar mechanism has been documented in Cameroon, where a decline in soil fertility results in falling cocoa yields, leading farmers to expand their cocoa farms into the forest to maintain production and farm revenues [69]. In this latter case, however, the immediate imperative is income from a cash crop rather than food production.…”
Section: Drivers Of Agricultural Expansion In Ssamentioning
confidence: 64%
“…Kebede, Baudron [58] found that the loss of soil fertility, and the subsequent negative impact on yields, combined with a need to sustain food production by the national level policy makers, is an important driver of agricultural expansion in the southern parts of Ethiopia. A similar mechanism has been documented in Cameroon, where a decline in soil fertility results in falling cocoa yields, leading farmers to expand their cocoa farms into the forest to maintain production and farm revenues [69]. In this latter case, however, the immediate imperative is income from a cash crop rather than food production.…”
Section: Drivers Of Agricultural Expansion In Ssamentioning
confidence: 64%
“…The level of nutrition is determined by the presence of major and minor elements required by the plant at each season and phenology of the tree. Therefore, how farmers manage the fertilization, depends on what they know of the soil quality conditions, which is reflected in the quantity and the quality of fruits produced by each plant per year; a basic aspect to be competitive in the subsector [10].…”
Section: Doi: 1018421/tem131-30mentioning
confidence: 99%
“…Similarly, the decrease in agricultural yields is a direct result of soil fertility loss (Schlecht et al, 2006). In the same vein, Kenfack Essougong et al (2020) state that the reduction in vegetation cover and loss of biodiversity are attributable to excessive soil exploitation, the use of fertilizers and pesticides, deforestation, and other factors contributing to degradation and increased erosion. Furthermore, our sampled producers claim that deforestation, driven by human actions to expand agricultural lands and pastures, is responsible for the reduction in vegetation cover and soil biodiversity (Bado & Bationo, 2018;Azare et al, 2020).…”
Section: Consequences Of Soil Degradation In the Sud Anian-sahelian Z...mentioning
confidence: 99%